2022
DOI: 10.1111/coa.13929
|View full text |Cite|
|
Sign up to set email alerts
|

Coblation intracapsular tonsillectomy: A cohort study of NHS practice in England using Hospital Episode Statistics

Abstract: Objectives To identify paediatric intracapsular Coblation tonsillectomy procedures from routine administrative data in England, and determine their safety. Design Retrospective observational cohort study of four ENT centres using routine data from Hospital Episode Statistics (HES). Setting Acute NHS trusts in England conducting exclusively intracapsular Coblation tonsillectomy. Participants Children (≤16 years old) undergoing bilateral intracapsular Coblation tonsillectomy. Main outcome measures Number of proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…This may have a lower risk of post‐operative haemorrhage, although haemorrhage rates following tonsil biopsy are not often reported; tonsil biopsy is often an exclusion criterion in publications discussing factors affecting post‐tonsillectomy haemorrhage rates 2 . A tonsil biopsy could be combined with intracapsular tonsillotomy if there are obstructive symptoms, which may have a lower bleeding rate than extracapsular techniques 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may have a lower risk of post‐operative haemorrhage, although haemorrhage rates following tonsil biopsy are not often reported; tonsil biopsy is often an exclusion criterion in publications discussing factors affecting post‐tonsillectomy haemorrhage rates 2 . A tonsil biopsy could be combined with intracapsular tonsillotomy if there are obstructive symptoms, which may have a lower bleeding rate than extracapsular techniques 12 …”
Section: Discussionmentioning
confidence: 99%
“…2 A tonsil biopsy could be combined with intracapsular tonsillotomy if there are obstructive symptoms, which may have a lower bleeding rate than extracapsular techniques. 12…”
Section: Number Of Malignant Diagnoses Malignant Diagnosesmentioning
confidence: 99%
“…Only 1.7% of claims were made after ICT as opposed to ECT, and the seven reported deaths were after ECT, exclusively [14 ▪ ]. In addition, a database review of English hospitals exclusively employing coblation ICT showed a 1.2% readmission rate and 0.2% reoperation rate for posttonsillectomy hemorrhage [15 ▪ ]. Revision tonsil surgery occurred in 0.3% at 1 year and 2.2% at 5 years [15 ▪ ].…”
Section: Safety and Regrowthmentioning
confidence: 99%
“…It could track the revision rate up to 5 years to be 2.2%. However, multiple centers and surgeons were involved, and the characteristic of the patients, including any existing comorbidities, were not analyzed 15 .…”
Section: Introductionmentioning
confidence: 99%